USES OF INTERNA ORGANS FOR BACTERIAL EVALUATION OF POULTRY CARCASSES - M.SHAMSHOON, SABAH; S.A.AL-MAYAH, ALI; S.HASSAN, ABBDE (The Iraqi Journal of Veterinary Medicine, 1996)
Eighteen birds were taken from a flock of line C and A,. They were reared on three types of litters, wood shaving, typha and blady grass until 7 weeks of age. After slaughtering and defeathering the carcasses were kept frozen. samples of breast and thigh muscles,liver and heart tissues were taken from the carcasses as well as samples of litters which were taken before and after rearing. The results showed that wood shaving contained less bacteria (P < 0.05) than the other two, before and after rearing. Litters from pens containing line C had less bacteria counts than that of line A. Samples from carcasses of line C revealed significantly (P <0.05) less bacterial counts than that of line A. Number of bacteria in liver and heart were significantly (P < 0.05) higher than those of breast and thigh muscles in both lines. Therefore, it seems to be advantageous to consider the sampling in internal organs (liver or heart) for determination of carcass" bacterial condition.